2014
DOI: 10.1111/tri.12312
|View full text |Cite
|
Sign up to set email alerts
|

Describing the evolution of medication nonadherence from pretransplant until 3 years post-transplant and determining pretransplant medication nonadherence as risk factor for post-transplant nonadherence to immunosuppressives: The Swiss Transplant Cohort S

Abstract: SummaryAlthough medication nonadherence (MNA) is a major risk factor for poor outcomes, the evolution of MNA from pre-to 3 years post-transplant among the four major organ transplant groups remains unknown. Therefore, this study described this evolution and investigated whether pretransplant MNA predicts post-transplant immunosuppressive medication nonadherence (IMNA). Adult participants (single transplant, pretransplant and ≤1 post-transplant assessment, using medications pretransplant) in the Swiss Transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
86
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 36 publications
6
86
0
3
Order By: Relevance
“…Em receptores de órgãos sólidos a não adesão pode aumentar com o passar do tempo após o transplante [22,23]. Ao contrário disso, neste estudo não houve diferença significativa quando relacionado o tempo após o transplante com a adesão.…”
Section: Discussionunclassified
“…Em receptores de órgãos sólidos a não adesão pode aumentar com o passar do tempo após o transplante [22,23]. Ao contrário disso, neste estudo não houve diferença significativa quando relacionado o tempo após o transplante com a adesão.…”
Section: Discussionunclassified
“…68 This finding was supported by a larger prospective nationwide cohort study of 1505 renal, liver, lung and heart transplant patients (OR, 3.10; 95% CI, 2.29-4.21). 66 Pretransplant self-reported nonadherence has also been found to be a predictor of acute rejection (OR, 4.4; 95% CI, 1.18-16.16). 68 The large impact that nonadherence has on treatment effectiveness is reflected in poor patient health outcomes, and increased healthcare costs.…”
mentioning
confidence: 99%
“…66 A prospective study of 141 lung, heart, and liver transplant patients showed that pretransplant nonadherence was a predictor of poor adherence posttransplant (OR, 7.9; 95% CI, 2. 35-26.8).…”
mentioning
confidence: 99%
See 2 more Smart Citations